Labor competences for public management and productivity of organic units of a provincial municipality - Vicente Herrera, Abigail Noemi (2020)
The objective of this research is to explain how labor competencies for public management affect the productivity of the organic units of the Jorge Basadre Provincial Municipality, in 2018. It is a basic type research - quantitative, not experimental, explanatory. In the present investigation, information has been taken from 108 workers, of the total population; A work skills test and a documentary record form were used as an instrument to record productivity data. The content validation was by expert opinion, the test of reliability of the test was performed using the Cronbach's Alpha method, having obtained an alpha indicator of 0.866 points. The results of the labor competencies, report an average of 44.54, according to the scale is in the regular level, the measurement of the indicators reports that 63.9% of those evaluated have a regular level of knowledge, 59.3% with regular skills and 67.6% with indifferent attitudes. The productivity results indicate a score of 49.14 which means a level of progress in progress, the analysis of the activities of each organic unit reports that the Project Liquidation Sub-Division has the lowest average with 26.67% and the Sub-Management Accounting has the highest average with 70.0%. The hypothesis test with Pearson's correlation coefficient r gives us the sig. Bilateral = 0.029 <0.05, therefore, the null hypothesis is rejected and the alternate hypothesis is accepted. In conclusion, if there is a significant effect of labor competencies on the productivity of the organic units of the Provincial Municipality of Jorge Basadre, in this way, confirming that there is a high positive correlation between labor competencies and productivity in the Provincial Municipality Jorge Basadre.